Characterizing interactions between Fusarium graminearum and Fusarium virguliforme on early soybean growth and development. Issue 2 (3rd April 2019) - Marburger, David A.; Smith, Damon L.; Conley, Shawn P.
Abstract: Fusarium graminearum and Fusarium virguliforme are two fungal pathogens that can infect soybean [ Glycine max (L.) Merr.] early in the growing season. A greenhouse experiment was conducted to determine if the presence of both pathogens resulted in an increased negative impact on early soybean growth compared with each pathogen alone. Treatment factors consisted of four inoculation treatments: a non-inoculated control, inoculation with F. graminearum only (FG), inoculation with F. virguliforme only (FV), and a combination of both pathogens (FG + FV). As well, three soybean cultivars (CH2105R2, P92Y51 and 'Sloan'), and three seed treatments (a control, mefenoxam + fludioxonil, and fluxapyroxad) were evaluated. Results indicated FG + FV did not result in increased root disease, a decrease in shoot growth, or reduced root growth compared with FG and FV. The FV inoculation treatment exhibited more root disease severity compared with FG, but there were no differences between the two inoculation treatments for the other below-ground measurements, as well as all above-ground measurements. Fungicide seed treatment did not reduce root disease severity or lead to increased early soybean growth compared with the non-treated control. Cultivar differences were the primary factor which influenced early-season soybean growth. Because there was no evidence of an increased effect between presence of F. graminearum and F. virguliforme, these results suggest management decisions for both pathogens can remain separate for soybean growers in Wisconsin, but management of F. virguliforme should take priority over F. graminearum due to its prevalent cause of soybean sudden death syndrome.